Assessing Local Government Capacity for Implementing Sustainable Transportation: The Role of Political Culture. Issue 5 (16th April 2017) - Irish, Aiden
ABSTRACT: Transportation development increasingly relies on local governments to implement sustainable strategies, yet implementation success varies widely. This begs an important question, why are some cities successful and others not? In response, this study focuses on the political culture characteristics of city leadership and staff pertaining to sustainable transportation. Employing semi-structured interviews with officials in two case study cities—Pomona and Pasadena, California—the study identifies and traces the impact of cultural characteristics on network interactions and the resulting transportation innovation. Finally, this research suggests key political and department characteristics that contribute to political cultures that facilitate sustainable transportation development.